To estimate the glucose and lipid profile levels in Diabetes without Nephropathy and in diabetic nephropathy patients - Maneesh Kumar Singh, Dr. Shreya Nigoskar (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Hyperglycemia, which results from impairments in insulin secretion, insulin action,or a combination of both, distinguishes diabetes mellitus (DM), a chronic metabolic condition. The way glucose metabolism and lipid homeostasis work together are a key part of how diabetic complications like nephropathy start and get worse. Aim: The study aimed to compare glucose and lipid profiles in diabetic patients without nephropathy with those affected by diabetic nephropathy